Couples and gender inequality - Kristian Larsen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2023)
This study shows that entering into a cohabiting partnership leads to long lasting earnings losses for women, even after accounting for the impact of child penalties. While 2 ⁄3 of the total effect of cohabitation is due to partnered women having higher fertility than unpartnered women, an income penalty of 5% is directly due to cohabitation, and not due to children. Cohabitation also reduces women's propensity to work evenings and weekends, and to hold a second job. The effects are temporary, and disappear if couples dissolve. I investigate household specialization and gender norms as potential mechanisms, and find that while specialization is unable to account for the effect, intergenerational transmission of traditional gender norms predicts the magnitude of the penalty. My analysis relies on a unique identification of cohabiting but otherwise informal partnerships in Danish administrative data.
Keywords: D63; D13; J12; J13; J16; 330; Cohabitation; Gender Inequality; Family Formation